Mengenalkan Keaksaraan Awal Dengan Bermain Kincir Angin (Huruf Vokal) Pada Kelompok Usia 4-5 Tahun Di TK Thoriq Bin Ziyad - Purwandi, Fadila Bela Anggraeni; Nirmala, Ine; Munafiah, Nida’ul (Peneliti.net, 2025)
Early literacy is one of the processes or stages to train children in reading. Early literacy is also a term used to describe a child's ability to use letters or to read and write that was mastered before the child learned how to read and write. So it can be concluded that early literacy is the ability of every child to recognize the letters and sounds of language. Then combine the letters into simple words. Vowels or vowels are sounds in spoken language characterized by open vocal cords so that no air pressure collects above the glottis. The vowels consist of A, I, U, E, and O. The purpose of playing using this windmill is to help children recognize vowels with fun and exciting activities. This study uses a qualitative research approach. The research method used is literature review or literature. The results of this study indicate that the variables x and y are correlated, at -27.641 and the critical t value (t table) is 1.753. In this case, 1.753 > 0.05, so Ho is rejected because it is much higher than the significance level of 0.05 and Ha is accepted.